Prevalence and Associated Factors of Contrast-Associated Acute Kidney Injury in Kidney Disease: A Retrospective Cohort Study - Meepornbucha, Kamonwan; Meenun, Wanniya; Srisakorn, Ponprom (Journal of the Nephrology Society of Thailand, 2025)
Background: Research indicates that the intravascular administration of contrast agents during computed tomography (CT) procedures may lead to Contrast-Associated Acute Kidney Injury (CA-AKI). The prevalence and associated risk factors for CA-AKI vary among different populations, particularly in individuals with pre-existing kidney disease. Methods: This retrospective cohort study included patients with an estimated glomerular filtration rate (eGFR) between 15 and 59 mL/min/1.73 m² who received intravenous contrast medium (CM) for CT between October 2021 and September 2024. The prevalence of CA-AKI in patients with kidney disease was evaluated, and associated risk factors were analyzed. Results: A total of 655 patients met the inclusion criteria. Among them, 58 patients (8.58%) developed CA-AKI. Baseline demographic characteristics were not significantly different between the CA-AKI and non-CA-AKI groups. However, the CA-AKI group had significantly higher proportions of patients with chronic kidney disease (CKD) stage G3b and G4, current use of diuretics and vasopressors, multiple exposures to CM within 72 hours, and concurrent acute kidney injury (AKI). Multivariate analysis identified CKD stage G3b (odds ratio [OR] 2.75; 95% confidence interval [CI], 1.26–6.00; p = 0.011) and current AKI (OR 3.99; 95% CI, 1.89–8.42; p < 0.001) as significant factors associated with the development of CA-AKI. Conclusions: CKD stage G3b and current AKI were significantly associated with an increased risk of CA-AKI. Therefore, caution is warranted when administering CM to patients with these conditions.